The Effect of Reliability, Flexibility, Satisfaction, Loyalty Moderated Price Fairness on Reuse Intention of Third Party Logistics Selection - Tantri Yanuar Rahmat Syah; Feri Putra Wilujeng*; Rojuaniah Rojuaniah; Ikramina Larasati Hazrati Hafidz; Diana Fajar Wati (Riwayat: Educational Journal of History and Humanities, 2023)
The purpose of this study is to investigate the relationship between reliability, flexibility, satisfaction, price fairness mediated loyalty, and reuse intention when choosing a 3PL service. The study used a targeted sample of 120 online sellers from various marketplaces. Data were analyzed using structural equation modeling (SEM) and SmartPLS 3.0. The study led to several discoveries. First, reliability has a positive impact on satisfaction. Second, flexibility has a positive impact on satisfaction. Third, flexibility has a positive impact on reuse intentions. Fourth, satisfaction has a positive impact on reuse intention. However, price fairness as a moderator between satisfaction and reuse intention did not have a significant effect on reuse intention. Finally, happiness has a positive effect on loyalty.